On Assessing ERA5 and MERRA2 Representations of Cold‐Air Outbreaks Across the Gulf Stream. Issue 19 (5th October 2021) - Seethala, C.; Zuidema, Paquita; Edson, James; Brunke, Michael; Chen, Gao; Li, Xiang‐Yu; Painemal, David; Robinson, Claire; Shingler, Taylor; Shook, Michael; Sorooshian, Armin; Thornhill, Lee; et al.
Abstract: The warm Gulf Stream sea surface temperatures strongly impact the evolution of winter clouds behind atmospheric cold fronts. Such cloud evolution remains challenging to model. The Gulf Stream is too wide within the ERA5 and MERRA2 reanalyses, affecting the turbulent surface fluxes. Known problems within the ERA5 boundary layer (too‐dry and too‐cool with too strong westerlies), ascertained primarily from ACTIVATE 2020 campaign aircraft dropsondes and secondarily from older buoy measurements, reinforce surface flux biases. In contrast, MERRA2 winter surface winds and air‐sea temperature/humidity differences are slightly too weak, producing surface fluxes that are too low. Reanalyses boundary layer heights in the strongly forced winter cold‐air‐outbreak regime are realistic, whereas late‐summer quiescent stable boundary layers are too shallow. Nevertheless, the reanalysis biases are small, and reanalyses adequately support their use for initializing higher‐resolution cloud process modeling studies of cold‐air outbreaks. Plain Language Summary: The Gulf Stream is a narrow band of warm water to the east of continental North America. As air moves eastward off of the continent, the warm ocean temperatures transfer moisture and heat that help develop and modify the marine low clouds. This transfer, particularly during cold‐air outbreaks present significant modeling challenges that contribute uncertainty to temperature projections for a world with more carbon dioxide. Simulations seeking to represent the details of such shallow clouds must rely on initializations and forcings that originate from coarser‐resolution reanalyses. Here we explore how well two major reanalyses and a commonly used flux product represent these fluxes and the boundary layer, using ocean buoy measurements and new in‐situ observations from an aircraft campaign. We find that the reanalyses are adequate for the purpose of initializing higher‐resolution modeling of the cold‐air outbreak clouds. In particular, the winter boundary layer heights are realistic. These heights are important for capturing winter cloud‐environmental interactions correctly. Late summer boundary layers are too shallow. Known biases do remain present, and impact the surface flux errors differently in the two reanalyzes examined. Key Points: Reanalysis surface fluxes and boundary layers are representative of observations to first‐order, sufficient for higher‐resolution model initialization Reanalyses represent the Gulf Stream more broadly than is seen in nature, contributing to turbulent flux and boundary layer biases Previously noted thermodynamic and dynamic biases reinforce (ERA5) or compensate (MERRA2) surface fluxes but support realistic winter boundary layer heights